N-Boc Amines to Oxazolidinones via Pd(II)/Bis-sulfoxide/Brønsted Acid Co-Catalyzed Allylic C–H Oxidation - Osberger, Thomas J. (American Chemical Society, 2014)
[Image: see text] A Pd(II)/bis-sulfoxide/Brønsted acid catalyzed allylic C–H oxidation reaction for the synthesis of oxazolidinones from simple N-Boc amines is reported. A range of oxazolidinones are furnished in good yields (avg 63%) and excellent diastereoselectivities (avg 15:1) to furnish products regioisomeric from those previously obtained using allylic C–H amination reactions. Mechanistic studies suggest the role of the phosphoric acid is to furnish a Pd(II)bis-sulfoxide phosphate catalyst that promotes allylic C–H cleavage and π-allylPd functionalization with a weak, aprotic oxygen nucleophile and to assist in catalyst regeneration.